Seroprevalence of hepatitis B virus co-infection among HIV-1-positive patients in North-Central Nigeria: The urgent need for surveillance - Terver M. Akindigh; Abba O. Joseph; Chrisitiana O. Robert; Ocheme J. Okojokwu; Juliet N. Okechalu; Aje J. Anejo-Okopi (AOSIS, 2019)
We report the seroprevalence of hepatitis B surface antigen among HIV-positive patients at a clinic in North-Central Nigeria. Screening for hepatitis B virus was based on serological markers. Alanine aminotransferase levels and CD4+ T-lymphocyte counts were compared between patients. The study showed that 9.2% were positive for hepatitis B surface antigen with significant differences between alanine aminotransferase levels of patients with and without hepatitis B virus. We recommend a national surveillance system to monitor control efforts.